Sustainability‐Related Supply Chain Risks: Conceptualization and Management. (19th July 2013) - Hofmann, Hannes; Busse, Christian; Bode, Christoph; Henke, Michael
ABSTRACT There is ample anecdotal evidence suggesting that firms can experience serious losses from social, ecological or ethical problems that exist in their supply chains. So far, however, research on supply chain risk management has largely neglected these sustainability issues. Most importantly, little is known about how sustainability issues manifest themselves as risks and how they create losses for focal firms. Without an in‐depth understanding of this materialization process, conceptualizations of sustainability risks will remain vague and effective management frameworks cannot be developed. We address this important research gap by means of a transdisciplinary approach and provide a concise description of how sustainability issues in supply chains materialize as risks for focal firms. Building on this mechanism and drawing on stakeholder theory, we develop a conceptualization of sustainability risks which lays the basis for future investigations in this respective field. In addition, we devise a viable management concept for sustainability‐related supply chain risks. The proposed concept can help firms to mitigate sustainability issues in global supply chains, thus making them less vulnerable to losses resulting from these risks. Its application will also foster sustainability standards within supply chains. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.